2004
DOI: 10.1111/j.1365-2567.2004.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Activator protein‐1 signalling pathway and apoptosis are modulated by poly(ADP‐ribose) polymerase‐1 in experimental colitis

Abstract: SUMMARYPoly(ADP-ribose) polymerase-1 (PARP-1) is activated in response to DNA injury in the nucleus of eukaryotic cells and has been implicated in intestinal barrier dysfunction during inflammatory bowel diseases. In this study we investigated whether PARP-1 may regulate the inflammatory response of experimental colitis at the level of signal transduction mechanisms. Mice genetically deficient of PARP-1 (PARP-1 -/-) and wild-type littermates were subjected to rectal instillation of trinitrobenzene sulphonic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…In further support of a direct role for JNK in intestinal pathophysiology, PARP-1 -/-mice were noted to have less severe TNBS-induced colitis in association with reduced JNK and AP-1 DNA binding activity [35]. Besides, previous data from our research group found that the expression and activity of p38 and JNK were increased in rats with TNBS-induced colitis.…”
Section: Page 15 Of 37mentioning
confidence: 72%
“…In further support of a direct role for JNK in intestinal pathophysiology, PARP-1 -/-mice were noted to have less severe TNBS-induced colitis in association with reduced JNK and AP-1 DNA binding activity [35]. Besides, previous data from our research group found that the expression and activity of p38 and JNK were increased in rats with TNBS-induced colitis.…”
Section: Page 15 Of 37mentioning
confidence: 72%
“…The first one identified was NFjB [16] providing an explanation at the molecular level for the protection of PARP-1 knockout mice from endotoxin shock. Several other transcription factors and cofactors involved in inflammatory regulation such as NFAT [17,18], AP-1 [19][20][21][22], YY1 [23], sp1 [24], SIRT1 [25,26] were also found to be modulated by PARP-1. Recent data pointed towards the involvement of other PARP enzymes in the transcriptional regulation of inflammatory processes.…”
Section: Transcription Factorsmentioning
confidence: 99%
“…PARP1 potentiates NF-B activity and AP-1 expression, fostering the expression of major NF-B and AP-1-depandant proinflammatory mediators (12). In intestinal epithelial cells in vitro, inhibition of PARP-1 with PJ-34 is protective during invasive Salmonella spp.…”
mentioning
confidence: 99%
“…Genetic ablation or pharmacological inhibition of PARP1 reduces the biological and physical manifestations of experimental colitis; Il-10 Ϫ/Ϫ mice treated with a PARP1 inhibitor (3-aminobenzamide) show a significant reduction in proinflammatory cytokine production associated with reduced intestinal permeability (6). Other PARP1 inhibitors have also been used successfully to prevent hapten-induced colitis in rats (7)(8)(9)(10)(11) and in mice (12,13). However, the mechanism(s) underlying PARP-mediated promotion of immune dysregulation in colitis remains unknown, although depletion of cellular energetic pools, which could culminate in cell dysfunction and necrosis as well as the promotion of the transcription of proinflammatory genes, has been postulated (2).…”
mentioning
confidence: 99%